PEMEKARAN DAERAH DAN KONFLIK KERUANGAN Kebijakan Otonomi Daerah dan Implementasinya di Indonesia - Harmantyo, Djoko (Makara Journal of Science, 2007)
Area divergence is a process to establish new autonomous region by dividing formerly local authority entity. This process was driven by the Regional Autonomy Law no. 32, 2004 which ensure decentralization mechanism to occur from. Spatial conflict is a term of interregional conflicts that is potentialy related to former administrative divided border line, which then will create border line dispute. This potential for any interregional relationship (including conflict) is a function neighbour number. According to an Internal Affairs report, thus recent phenomena of local divided authorities has been escalating in Indonesia. Since 1999-2005, there has been 148 new local autonomous governments or more than thirty new additional local autonomus government were born annualy. There are two main questions arise from these issues (1) what is the ideal number of local autonomous government in Indonesia, and (2) what is the quantity of interregional relationship needed to relate spatial conflicts. Based on the central place theory and a spatial conflicts model the ideal number of autonomous districts in Indonesia is 460 of kabupaten/kota and 46 provinces. Theoretically, they need 2760 forms of interregional relationships or six relationship forms in each local government to eliminate the spatial conflict potentialy. Rearrangement of regional autonomous policy focusing on the implementation of areal divergences shall be done as quickly as possible.